Design and fabrication of a 3D printed acoustic levitator for droplet trapping - Yap, Nelson Jia Jun (Nanyang Technological University, 2020)
Acoustic levitation in single-axis acoustic levitator occurs when a standing wave is formed between a transducer and a correctly positioned reflector plate or another transducer. Light objects and liquids can be manipulated in midair when placed at the nodes in a standing wave. Acoustic levitation along a single axis can be formed with a pair of transducers, a transducer, and a reflector, or by an array of multiple transducers. In acoustic levitation, to drastically improve the axial forces and radial forces acting on the suspended objects, concave surfaces, and self-adaptive reflectors are utilised. This report will discuss the design, fabrication and operation of single-axis non resonant acoustic levitator. The levitation of light objects and liquid with the help of single-axis acoustic levitator and achieve maximum acoustic pressure force by varying the arrangement, numbers, and geometry of transducers.